Continuous Renal Replacement Therapy in Acute Brain Injury - Cruz-Llanos, Luis; Molano, Alejandra; Rizo-Topete, Lilia (Frontiers in Nephrology, 2022)
Acute brain injury is the sudden and reversible loss of brain self regulation capacity as a disruption of the blood-brain barrier that conditions metabolic and inflammatory disorders that can exacerbate acute kidney injury in a critical setting; specifically it has been described that the alterations of the internal environment that come from the severity of the acute kidney injury increases the risk of endocranial hypertension and cerebral edema; in this context, injuries should be identified and treated in a timely manner with a comprehensive approach. Continuous kidney replacement therapy is an extracorporeal purification technique that has been gaining ground in the management of acute kidney injury in critically ill patients. Within its modalities, continuous venous venous hemofiltration is described as the therapy of choice in patients with acute brain injury due to its advantages in maintaining hemodynamic stability and reducing the risk of cerebral edema. Optimal control of variables such as timing to start renal replacement therapy, the prescribed dose, the composition of the replacement fluid and the anticoagulation of the extracorporeal circuit will have a significant impact on the evolution of the neurocritical patient with acute kidney injury. There are limited studies evaluating the role of hemofiltration in this context.